Social media marketing communications of convenience store franchises in Taiwan - Wang, Huai Yin; Stříteský, Václav; Kottika, Efthymia, 1982-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
Social media has transformed the communication between business and customers and become a vital marketing communication tool for firms to facilitate customer engagement. The objective of the thesis is to compare the post strategies of the top four convenience store franchises in Taiwan on Facebook and Instagram and to identify certain social media posts characteristics, including post timing, post media type, content characteristics and content type, that effectively increase consumer engagement on social media platforms. The research was conducted through content analysis of the brand posts on the two social media platforms and statistical analysis based on the result of the content analysis. The result of content analysis showed that there were discrepancies between the level of customer engagement and posting strategies among the four brands. The result of statistical analysis revealed that post timing in a day and content characteristics, including number of emojis and hashtags used per post, text length, and content types, were factors influencing customer engagement rate for the convenience stores franchises on the examined platforms. Based on the findings, recommendation was provided for convenience store franchises to enhance their social media marketing communications strategies in the Taiwanese market.
Vedoucí práce: Václav Stříteský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses